Reflexology On Blood Sugar Levels In Patients With Diabetes Mellitus: Literature Review - Wiratama, Rahardyan Dika; Muhith, Abdul; Zahro, Chilyatiz (Chakra Brahmanda Lentera Institute, 2023)
Background: Diabetes mellitus is a disease that often causes chronic complications if not handled properly and is characterized by an increase in blood sugar levels. This literature review aims to determine the effect of reflexology on blood sugar levels in patients with diabetes mellitus. Methods: The method used in this article is a literature review using a journal database from Science Direct and Google Scholar from 2020 to 2023 with the keywords